Prenatal exposure to persistent organic pollutants and methylation of LINE-1 and imprinted genes in placenta: A CHECK cohort study. (October 2018) - Kim, Sujin; Cho, Yoon Hee; Lee, Inae; Kim, Wonji; Won, Sungho; Ku, Ja-Lok; Moon, Hyo-Bang; Park, Jeongim; Kim, Sungkyoon; Choi, Gyuyeon; Choi, Kyungho
Abstract: Prenatal exposure to persistent organic pollutants (POPs) has been linked to numerous adverse birth outcomes among newborn infants in many epidemiological studies. Although epigenetic modifications have been suggested as possible explanations for those associations, studies have rarely reported a relationship between POP exposure during pregnancy and DNA methylation in the placenta. In the present study, we investigated the association between prenatal exposure to several POPs, including organochlorine pesticides (OCPs), polybrominated diphenyl ethers (PBDEs), and polychlorinated biphenyls (PCBs), and methylation levels of long interspersed element 1 (LINE-1), as well as imprinted genes in placental DNAs among Korean mother-child pairs (N = 109). We assessed the association of DNA methylation not only with each target POP (single-POP models) but also with multiple POPs applying principal component analysis (multiple-POP models). Potential associations between placental DNA methylation and birth outcomes of newborn infants were also estimated. In single-POP models, significant associations were detected between OCP measurements and placental DNA methylation. Elevated concentrations of β-hexachlorhexane (β-HCH) in maternal serum collected during delivery were significantly associated with a decrease in methylation of LINE-1 in the placenta. Higher levels of p, p ′-dichlorodiphenyltrichloroethane ( p, p ′-DDT) in maternal serum were associated with hypermethylation of insulin-like growth factor 2 ( IGF2 ). In multiple-POP models, a significant and positive association between DDTs and IGF2 methylation was also observed. Placental LINE-1 methylation was inversely associated with birth length. Our observations indicate that prenatal exposure to several POPs including DDTs is associated with the changes in methylation of genes, including major imprinted genes in the placenta. The consequences of these epigenetic alterations in placenta during development deserve further investigation. Highlights: Associations between POP exposure and placental DNA methylation were evaluated. A multi-pollutant exposure was added in the models with principal component analysis. Exposure to DDTs, including p, p ′-DDT, was related to methylation of IGF2 in the placenta. Several POPs might affect epigenetic regulation of key placental DNAs.